Comparing Probiotics Plus Lactulose with Lactulose Alone in Treatment of Overt Hepatic Encephalopathy: Probiotics Plus Lactulose with Lactulose in Treatment of Overt Hepatic Encephalopathy - Ahmad, Omer Hassaan Aftab; Hafeez, Amtul; Asif, Aiman; Amjad, Ammarah; Tayyab, Mehwish; Mumal, Sidra; Ali, Mashhood (Pakistan Journal of Health Sciences, 2025)
A neuropsychiatric condition known as hepatic encephalopathy (HE) is brought on by liver malfunction, which accumulates poisons like ammonia and impairs brain activity. Objectives: To compare the viability of combining probiotics with lactulose versus utilizing lactulose alone within the treatment of obvious hepatic encephalopathy. Methods: This quasi-experimental study took place in the Gastroenterology and Hepatology Department at the Pakistan Institute of Medical Sciences in Islamabad from August 2019 to January 2020. A total of 160 patients diagnosed with overt HE were included and divided into two groups. Group A received a combination of probiotics and lactulose, while Group B received lactulose alone. Treatment outcomes were evaluated over six months based on improvement in HE symptoms, Model for End-Stage Liver Disease (MELD) scores, length of hospital stay, and potential precipitating factors. Results: The mean age of participants was 44.08 ± 11.31 years. Group A comprised 64 males (80%) and 16 females (20%), while Group B had 30 male (37.5%) and 50 female (62.5%). The MELD scores were comparable between groups (p=0.648). However, the mean hospital stay was significantly shorter in Group A (2.34 ± 0.56 days) than in Group B (2.42 ± 0.63 days; p<0.05), indicating enhanced recovery in the combination therapy group. Conclusions: The addition of probiotics to lactulose significantly improves clinical outcomes in patients with overt hepatic encephalopathy by reducing hospital stay and enhancing treatment efficacy.